Paeonol Protects Against Myocardial Ischemia/Reperfusion-Induced Injury by Mediating Apoptosis and Autophagy Crosstalk - Tsai, Chin-Feng; Su, Hsing-Hui; Chen, Ke‐Min; Liao, Jiuan-Miaw; Yao, Yi-Ting; Chen, Yi-Hung; Wang, Meilin; Chu, Ya-Chun; Wang, Yi-Hsin; Huang, Shiang-Suo (Frontiers in Pharmacology, 2021)
Many studies have shown that crosstalk exists between apoptosis and autophagy, despite differences in mechanisms between these processes. Paeonol, a major phenolic compound isolated from Moutan Cortex Radicis, the root bark of Paeonia x suffruticosa Andrews (Paeoniaceae), has been widely used in traditional Chinese medicine as an antipyretic, analgesic and anti-inflammatory agent. In this study, we investigated the detailed molecular mechanisms of the crosstalk between apoptosis and autophagy underlying the cardioprotective effects of paeonol in rats subjected to myocardial ischemia/reperfusion (I/R) injury. Myocardial I/R injury was induced by occlusion of the left anterior descending coronary artery (LAD) for 1 h followed by 3 h of reperfusion. Paeonol was intravenous administration of paeonol 15 min before LAD ligation. We found that paeonol significantly improved cardiac function after myocardial I/R injury and significantly decreased myocardial I/R-induced arrhythmia and mortality. Paeonol also significantly decreased myocardial infarction and plasma LDH activity and troponin I levels in carotid blood after I/R. Treatment with paeonol not only caused significant upregulation of Bcl-2 protein expression, but also significant downregulation of the cleaved form of caspase-8, caspase-9, caspase-3 and PARP proteins expression in the I/R injured myocardium compared with those in vehicle-treated controls. We also found that the myocardial I/R-induced autophagy, including the increase of Beclin-1, p62, LC3-I, and LC3-II protein expression, in the myocardium was significantly reversed by paeonol treatment. Furthermore, paeonol also significantly increased the ratios of Bcl-2 to Bax and Bcl-2 to Beclin-1 in the myocardium after I/R injury. The cardioprotective role of paeonol during I/R injury may be due to its mediation of crosstalk between apoptotic and autophagic signaling pathways, inhibiting apoptosis and autophagic cell death.